Sustainable increase in livestock productivity in developing countries through efficient utilisation of feed resources - Makkar, Harinder P. S. (Cuban Journal of Agricultural Science, 2014)
During last several decades world production of animal products has increased rapidly. Due to increasing incomes and economic growth, urbanization and population growth, the livestock will continue to be the most dynamic sub-sector of agriculture in the coming decades. The world would require 60-70% more meat and milk than the current consumption levels. Besides energy, availability of feed would be critical to meeting the projected demand of animal products. This is amidst growing concerns over scarcity of land, soil and water, food-feed-fuel competition and on-going global warming. In developing countries, the inability of farmers to feed animals adequately remains the major constraint in most livestock production systems. A concerted effort is required to sustainably meet the future rising demands of feed ingredients and feeds. The strategies that could address this challenge are: I) assess available feed resources and make the best use of them, II) enhance fodder availability and its use in place of concentrate component in the diet, which is expensive and contains components competing with human food, III) enlarge the feed resource base by tapping into new and unconventional resources that do not compete with human food, including the plants that are adapted to the region and IV) enhance nutrient absorption from feeds by strategically using anthelmintics and mineral and vitamin mixtures in diets. In order to enhance livestock productivity, these efforts should go hand-in-hand with the use of proper animal genetic resources that match the environment, and the adoption of good management practices including provision of clean drinking water, and good animal comfort and health. An enhanced emphasis is required to increase nutrient use efficiency in ruminant production systems because ruminants have special place in the animal food value chain since they do not compete with human food and can produce human-edible animal protein from human-inedible sources such as grasses, crop residues and agro-industrial by-products.